Evaluasi Program Revitalisasi Lapangan Motang Rua Kabupaten Manggarai - Yohana Dwi Fernanda; Nursalam Nursalam; Jim B. Kolianan (Jurnal Media Administrasi, 2026)
Public space revitalization is an important strategy in urban development aimed at improving the quality of urban environments while stimulating social interaction and local economic activities. This study aims to evaluate the implementation of the Motang Rua Field revitalization program in Manggarai Regency and assess the extent to which the program achieved its intended development objectives. The study employed a qualitative descriptive approach. Data were collected through field observations, in-depth interviews with key informants including local government officials, project contractors, small business actors, and community members, as well as documentation related to the revitalization program. Data were analyzed through data reduction, data display, and conclusion drawing, supported by triangulation techniques to ensure data validity. The findings indicate that the revitalization program demonstrates a high level of relevance to community needs and aligns with the regional development vision of Ruteng Kota Molas. The implementation process shows strong coherence through effective inter-institutional coordination and consistency between planning and execution. The revitalization has also proven effective in improving public facilities, enhancing community social activities, and stimulating local economic growth through increased micro and small business activities. Furthermore, the program was implemented efficiently in terms of budget management and project timeline. The revitalization also contributes to strengthening socio-cultural values through the preservation of the historical figure Motang Rua and shows strong sustainability potential through increased public utilization of the revitalized space.